2020
DOI: 10.1017/s0022029920000606
|View full text |Cite
|
Sign up to set email alerts
|

The human−animal relationship in dairy animals

Abstract: The present study aims to identify margins for the improvement of dairy animal welfare and production based on the quality of the human−animal relationship (HAR). The main tool proposed to improve the quality of HAR in dairy animals is training of stock-people by targeting their attitude and behaviour. Given that a good quality HAR may benefit the welfare of dairy animals and productivity, new technologies, by monitoring the handling routine on farm, may be more effective in promoting good practices. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
0
16
0
5
Order By: Relevance
“…In 2020 was published Comunicação emocional entre o homem e o animal não humano [29], a literature review on emotional communication between human and nonhuman animals, The Power of a Positive Human-Animal Relationship for Animal Welfare [5]; Effects of Long-Term Gentle Handling on Behavioral Responses, Production Performance, and Meat Quality of Pigs [30]; Farmers' representations of the effects of precision livestock farming on the human-animal relationship [31]; The human−animal relationship in dairy animals [32], and Stockpeople and Animal Welfare: Compatibilities, Contradictions, and Unresolved Ethical Dilemmas [33].…”
Section: State Of the Artmentioning
confidence: 99%
“…In 2020 was published Comunicação emocional entre o homem e o animal não humano [29], a literature review on emotional communication between human and nonhuman animals, The Power of a Positive Human-Animal Relationship for Animal Welfare [5]; Effects of Long-Term Gentle Handling on Behavioral Responses, Production Performance, and Meat Quality of Pigs [30]; Farmers' representations of the effects of precision livestock farming on the human-animal relationship [31]; The human−animal relationship in dairy animals [32], and Stockpeople and Animal Welfare: Compatibilities, Contradictions, and Unresolved Ethical Dilemmas [33].…”
Section: State Of the Artmentioning
confidence: 99%
“…The human-dairy cattle interaction and its effects on milk production and welfare status have been extensively examined [10,20,22,39]. Aversive handling and forceful, negative tactile interactions are generally associated with fear, high signs of nervousness, a reluctance to move to the milking parlour, baulking, an increased number of vocalizations or steps [10,20,22], a decreased proportion of conceiving to the first insemination [20], a reduction of the milk yield and a deterioration of the milk quality (i.e., reduced protein and fat levels) [10,20] in dairy cows.…”
Section: Human-dairy Animal Interaction 21 Dairy Cattle and Buffaloesmentioning
confidence: 99%
“…To meet community demands, targeted cognitive-behavioural training programs and specific protocols aimed at the handling improvement are therefore necessary in dairy farms in order to maintain an improved welfare status and production efficiency [39]. Undoubtedly, the attitudes and skills of the farmer and his/her familiarity with the animals are very important; however, there are also issues-such as job satisfaction and motivation, working conditions and organisational policies and rules-that modify handling practices [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…Cows can suffer from heat stress during spring–summer, which impacts their milk production and its quality. It has been reported that heat stress (a temperature humidity index (THI) above 68) negatively impacts their welfare [ 28 ], milk production, and its yield and fat content [ 29 , 30 , 31 , 32 ], as well as the milk’s FAP [ 33 ]. Salamon et al [ 34 ] showed higher percentages of C18:2, C18:3 (n-3), C18:1 (Oleic), and CLA in milk obtained during summer compared to those in milk from winter.…”
Section: Introductionmentioning
confidence: 99%